2022
DOI: 10.1128/mbio.03005-21
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CD16+Extracellular Vesicles Associate with Carotid Artery Intima-Media Thickness in HIV+Adults on Combination Antiretroviral Therapy

Abstract: HIV-infected individuals have a 2-fold-increased risk of cardiovascular disease compared with the general population, yet the mechanisms underlying this comorbidity are unclear. Extracellular vesicles have emerged as important mediators in cell-cell communication and, given what we know of their biology, may drive inflammation contributing to cardiovascular disease in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…We mimicked the conditions in the bloodstream in vivo as closely as possible, by studying the autologous blood EVs present in plasma directly, without ultracentrifugation. The results obtained with this direct phenotyping method were similar to published results, particularly for the phenotyping of EVs in HDs ( 2 , 3 , 14 ).. This direct plasma EV phenotyping also revealed heterogeneity in the numbers and size distribution of EVs ( Supplemental Table 1 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We mimicked the conditions in the bloodstream in vivo as closely as possible, by studying the autologous blood EVs present in plasma directly, without ultracentrifugation. The results obtained with this direct phenotyping method were similar to published results, particularly for the phenotyping of EVs in HDs ( 2 , 3 , 14 ).. This direct plasma EV phenotyping also revealed heterogeneity in the numbers and size distribution of EVs ( Supplemental Table 1 ).…”
Section: Discussionsupporting
confidence: 86%
“…However, sCD27 may also be provided by CD27 + EVs during culture. Indeed, the presence of CD27 + EVs has recently been reported in the plasma of HIV-infected patients ( 14 ). We purified CD27 + EVs by flow cytometry to test this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…High plasma sCD27 concentrations are associated with poor patient survival ( 9 ). A vesicular form of CD27 has been found in plasma from healthy blood donors (HDs) ( 12 , 13 ). Two types of extracellular vesicle have been identified: exosomes (small vesicles, 40-100 nm in diameter, derived from intracellular membrane compartments), and larger extracellular vesicles (200-900 nm in diameter, generated by the budding of the cell membrane) known as microparticles (MPs) or ectosomes ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…A 0.22 µm-filtered PBS control was recorded to estimate the background signal. EV gates were established 100 nm (Invitrogen) to 1000 nm beads (Megamix: 160, 200, 240 and 500 nm; Spherotech 1000 nm) ( 26 , 41 , 42 ). Representative flow cytometry plots are shown in Figure 1C .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we recently showed that plasma-EVs expressing monocyte markers are associated with carotid artery intima-media thickness in HIV-infected individuals on virologically suppressive ART. We further showed that the EV fraction from HIV+ adults on stable ART induced endothelial cell death via necrosis of human umbilical vein endothelial cells ( 26 ). These properties make EVs potential candidates as targets of immunotherapies and putative biomarkers for diseases ( 17 , 27 30 ).…”
Section: Introductionmentioning
confidence: 99%